A Community Based Systems Diagram of Obesity Causes - Allender, Steven; Owen, Brynle; Kuhlberg, Jill; Lowe, Janette; Nagorcka-Smith, Phoebe; Whelan, Jill; Bell, Colin (PLOS ONE, 2015)
Introduction Application of system thinking to the development, implementation and evaluation of childhood obesity prevention efforts represents the cutting edge of community-based prevention. We report on an approach to developing a system oriented community perspective on the causes of obesity. Methods Group model building sessions were conducted in a rural Australian community to address increasing childhood obesity. Stakeholders (n = 12) built a community model that progressed from connection circles to causal loop diagrams using scripts from the system dynamics literature. Participants began this work in identifying change over time in causes and effects of childhood obesity within their community. The initial causal loop diagram was then reviewed and elaborated by 50 community leaders over a full day session. Results The process created a causal loop diagram representing community perceptions of determinants and causes of obesity. The causal loop diagram can be broken down into four separate domains; social influences; fast food and junk food; participation in sport; and general physical activity. Discussion This causal loop diagram can provide the basis for community led planning of a prevention response that engages with multiple levels of existing settings and systems.